STRATEGI HUMAS KEMENKOMINFO DALAM MENCIPTAKAN CITRA POSITIF DITJEN POSTEL DI KALANGAN STAKEHOLDERNYA - Lestari, Putri Cahaya (Universitas Prof. Dr. Moestopo (Beragama), 2012)
Public Relations practise is deliberate, planned and sustain effort to establish and maintain mutual understanding between an organizational and its public. Public relations as good image maker for Indonesia communication and information ministry has strategy for internal and eksternal public. Four step program public relations with researching, planning, implementing and evaluating to make positive image of the Indonesia communication and information ministry. Employee relations aktivities such as traning, workshop, in house bulletin are the implementation of the internal strategy. Media relations activities for eksternal public : press release, press tour, coffe morning building the positif image of Kemenkominfo.